P56 The evolving role of the Hepatology Pharmacist at St George's Hospital. (20th September 2022) - Boothman, Miss Helen; Reynolds, Kieran; Clark, Sarah; Forton, Daniel
Abstract : The recent Improving Quality in Liver Services (IQILS) accreditation at St George's University Hospitals NHS Foundation Trust (SGH) identified the pharmacist contribution as an exemplar part of the service provided by the hepatology team. A dedicated hepatology pharmacist was first appointed in 2015, the hepatitis C CQUIN providing an invaluable opportunity for specialist hepatology pharmacists as it mandated the inclusion of a pharmacist as part of the multidisciplinary team (MDT). The role has evolved since then, initially clinics focused on the provision of adherence and complex drug-drug interaction checks in hepatitis C. Now, the hepatology pharmacy service manages a cohort of patients with hepatitis C, hepatitis B; including antenatal patients with hepatitis B and patients at risk of hepatitis B reactivation, primary biliary cholangitis (PBC) and autoimmune hepatitis (AIH), with 1, 088 outpatient appointments booked between April 2021-March 2022, as compared to 89 patients in 2015/16. The value of pharmacists in outpatient clinics is well recognised; in promoting medication adherence, medication safety, assisting in improving patient outcomes and promoting the quality use of medicines. A recent patient experience survey showed 100% (n = 40) of patients were happy or very happy with the pharmacist-led hepatology clinic. At SGH, clinic protocols were developed to ensure safe, effective and independent management of these patient cohorts, recognising the limitations and referral points of the hepatology pharmacist led clinics. The skills of a pharmacist are utilised in the clinics, with more frequent monitoring (inc. therapeutic drug monitoring) of patients compared to a traditional consultant led clinic model, ensuring patient safety and improving patient experience. The patient experience survey showed 100% (n=40) felt their condition was managed well in the pharmacist-led clinic with 97.5% (n = 39) feeling supported and comfortable that they could discuss any concerns they had about their condition and that these were addressed. Pharmacists act as a point of contact for patients, providing medication supply and advice outside their scheduled appointments, between April 2021 – March 2022, 843 prescriptions were supplied outside clinic appointments preventing missed doses. There has been continued contribution to the inpatient hepatology cohort on ward rounds to ensure medicines optimisation, improve patient safety and the safe, effective and cost-effective use of medicines. Interventions are tracked and cost avoidance can be proven. Pharmacists are an integral part of the hepatology team at SGH and will continue to work in the MDT to provide the best possible care to patients. References: Hayward KL, Patel PJ, Valery PC, Horsfall LU, Li CY, Wright PL, et al . Medication-related problems in outpatients with decompensated cirrhosis: opportunities for harm prevention. Hepatol Commun 2019;3 :620–31. Williams T, Purvis TL. Development of an outpatient pharmacist-managed clozapine clinic. Am J Health-Syst Pharm 2012;69 :1192–5. Fuertes F, Soliman A, Bullas D. Evaluation of a pharmacist-led virtual thiopurine clinic. The Pharmaceutical Journal 2020. Accessed online June 2022: